Degradation recognition and residual life analysis of gasifier firebrick in service using Hidden Semi-Markov Model. (1st February 2023) - Zhang, Jinchun; Xv, Feiyu; Hou, Jinxiu
Abstract: The firebricks in gasifier combustion chamber are the vital parts for gasification. They are gradually degraded with service time due to the harsh conditions. This paper focuses on the recognition of degradation of firebricks and analysis of their residual life, which are of great significance for ensuring the safe operation of a gasifier. In this paper, the Hidden Semi-Markov Model (HSMM) was employed and the degradation recognition and residual life analysis of the firebricks in a gasifier combustor of a company under actual working conditions were carried out. The results show that the degradations of firebricks in the jet area of cylinder part are faster than that in the arch crown and the pipe area. In the early and middle stages of firebrick life, the transformation of its degradation state takes longer time than in the later stage of firebrick life. And the residual life of each layer firebrick is short in the later stage of the firebrick life. The residual life of firebricks in the jet area of cylinder part is shorter than that in the jet area of arch crown and pipe area. HSMM method is a suitable method that provides new solutions for firebrick maintenance strategies. Highlights: HSMM was used for degradation and residual life analysis of firebricks in gasifier. The degradation rate of firebricks in the jet area of the cylinder is the fastest. The residual life of firebricks in the jet area of the cylinder is the shortest. The HSMM method provides a new solution for firebrick maintenance strategies.